2012
DOI: 10.1098/rsta.2012.0024
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the central molecular zone of the Galaxy using spectroscopy of H 3 + and CO

Abstract: The central 400 parsecs of the Milky Way, a region known as the central molecular zone (CMZ), contains interstellar gas in a wide range of physical environments, from ultra-hot, rarified and highly ionized to warm, dense and molecular. The combination of infrared spectroscopy of H + 3 and CO is a powerful way to determine the basic properties of molecular interstellar gas, because the abundance ratio of H + 3 to CO in 'dense' clouds is quite different from that in 'diffuse' clouds. Moreover, the energy-level s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…3 that even for ∆t = 500 yr, the model slightly underestimates the measured 6.4 keV line flux at longitudinal distances from Sgr A * of ∼ 1 • . This suggests that the warm and diffuse gas extends beyond the CMZ, which might be already suggested by the measured outwards movement of this gas component (see Geballe 2012).…”
Section: Cosmic Rayssupporting
confidence: 62%
See 1 more Smart Citation
“…3 that even for ∆t = 500 yr, the model slightly underestimates the measured 6.4 keV line flux at longitudinal distances from Sgr A * of ∼ 1 • . This suggests that the warm and diffuse gas extends beyond the CMZ, which might be already suggested by the measured outwards movement of this gas component (see Geballe 2012).…”
Section: Cosmic Rayssupporting
confidence: 62%
“…These authors also suggested that the remaining 90% of the X-ray emission is produced by interactions of electrons with a denser (n ∼ 10 3 cm −3 ) molecular gas. But this would imply the existence of a massive (∼ 10 7 M ⊙ ) molecular gas component with a high ionization rate (ζ 2 > ∼ 10 −14 s −1 ), which should have been detected with H + 3 observations (see, e.g., Geballe 2012). Independent of the exact density of the diffuse molecular gas, the comparison of the cross sections σ Kα iFe and σ ioni iH2 (Fig.…”
Section: Cosmic Raysmentioning
confidence: 85%
“…Since the first report by Geballe and Oka [71] of detected H + 3 absorption from measurements of the stellar objects GL2136 and W33A, the ISM has also been the goal of different investigations [72][73][74]. The spectroscopic study of this species has been employed as a way to explore central regions of the Galaxy [75][76][77], to analyse cosmic ray ionization rates [78][79][80][81][82] and to investigate star formation regions [83][84][85][86][87].…”
Section: Presence In Spacementioning
confidence: 99%
“…Geballe (2012) stated that N(3, 3)/N(1, 1) is a good thermometer for any temperature and N(3, 3)/N(2, 2) is a good densimeter for high temperature; see discussion in Oka (2013). Oka & Epp (2004) computed maps of these ratios in the plane n(H 2 )-T and deduced that the gas probed by H + 3 in the CMZ is diffuse (n(H 2 ) ≤ 70 cm −3 ) and warm (T ≥ 300 K).…”
Section: Excitationmentioning
confidence: 99%